The Challenge of Ideological Neutrality in Digital Content: An Examination of the Perception of Human Capital Managers in a Corporate Setting - Bondan Ari Wijaya (Sustainable Human Capital Development Journal, 2026)
The rise of social media has blurred the boundaries between personal and professional lives, particularly for managers in large organizations. This study aims to explore how social media posts by Human Capital (HC) managers affect employee perceptions of their image, credibility, and neutrality. The primary research objectives are to: (1) examine the influence of social media posts on employee trust, (2) identify factors that improve or harm managerial credibility, and (3) develop strategies for managing digital reputations. The study adopts Goffman’s Impression Management Theory and Social Identity Theory to analyze the relationship between digital behavior and professional image. A descriptive qualitative methodology was used, incorporating in-depth interviews, case studies of sensitive social media posts, and document analysis of corporate policies. Findings indicate that posts related to luxury lifestyles or political opinions can polarize employee perceptions, while posts focused on professional development reinforce a positive image. This research emphasizes the importance of ethical digital communication and offers practical implications for managing HC managers' online personas to build sustainable trust within organizations